1977
DOI: 10.1148/124.3.723
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Role of CT Scanning of the Pancreas

Abstract: In a group of 188 patients, 192 computed tomographic (CT) scans of the pancreas were done, and the diagnostic accuracy of CT determined relative to other modalities. CT was the most effective method of detecting neoplastic and inflammatory diseases. The full extent of the disease process, including involvement of the retroperitoneum and metastasis to the liver, was visualized with one examination. Calcification and cystic collections associated with pancreatitis were also clearly seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…1980], Haaga et al [1977] compared the value of CT in demonstrating pancreatic location with other diagnostic procedures such as angiography and ultrason ography. They reported that measurements of normal pancreas performed on 31 autopsy specimens correlated well with CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…1980], Haaga et al [1977] compared the value of CT in demonstrating pancreatic location with other diagnostic procedures such as angiography and ultrason ography. They reported that measurements of normal pancreas performed on 31 autopsy specimens correlated well with CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…Initial experience with the method, as applied to the pancreas, has recently been reported from two major American institutions (Haaga et al, 1977;Sheedy et al, 1977). Changes in the size and shape of the gland are reliably detected but no difference in density between neoplastic and normal tissue has been seen.…”
Section: Visualisation Of Lesser Sacmentioning
confidence: 99%
“…Widening of the pancreatic duct existed in both groups; mass shadow was hardly detected in localized and rather easily detected in extensive cancer; duodenal invasion and obliteration of fat planes were found only in extensive type; enlargement of the pancreas was a confusing factor of tumor detection in localized type; atrophy of the pancreatic body and tail was a most favorable indirect sign in extensive cancer.of pancreas -Pancreatic neoplasms Computed tomography has been anticipated as a useful method for detecting tumor in the head of the pancreas [1][2][3][4][5]. However, correlations between tumor staging and CT findings were not fully explained.…”
mentioning
confidence: 99%
“…of pancreas -Pancreatic neoplasms Computed tomography has been anticipated as a useful method for detecting tumor in the head of the pancreas [1][2][3][4][5]. However, correlations between tumor staging and CT findings were not fully explained.…”
mentioning
confidence: 99%